Protective effect of MiR-146 on renal injury following cardiopulmonary bypass in rats through mediating NF-κB signaling pathway. Issue 1 (1st January 2022) - Ma, Hongbo; Dong, Yanjiao; Sun, Kun; Wang, Shuo; Zhang, Zheng
ABSTRACT: The mechanism of renal injury after cardiopulmonary bypass is not clear, and the protective effect of microRNA-146 through mediating NF KB signaling pathway needs to be verified. The study intends to establish a rat model of cardiopulmonary bypass (CPB). MiR-146 is silenced or overexpressed by lentivirus transfection. It is divided into miR-146 inhibitors group (inhibitors), miR-146 mimics group (mimics) and sham group. It is found that the contents of Cr, bun and MDA in blood = , serum IL-1, IL-6 and TNF in mimics group are higher than those in the other two groups- α Content, apoptosis rate, ICAM-1, TNF- α, NF- κ B mRNA and NF- κ B protein decreased significantly (P < 0.05), while the content of SOD in kidney increased significantly (P < 0.05). In the inhibitors group, the above indicators showed the opposite results. Double luciferase assay showed that NF-kB was the target gene of miR-146. It can be seen that the expression of miR-146 inhibits inflammatory factors, apoptosis, oxidative stress and NF- κ the activation of B pathway promotes the repair of renal injury in CPB rats.